Exploring strategies to connect formerly incarcerated individuals with community pharmacist-administered injectable naltrexone services - Chladek, Jason S.; Chui, Michelle A. (Frontiers in Public Health, 2025)
IntroductionFor formerly incarcerated individuals with opioid use disorder (OUD), the use of medications for opioid use disorder (MOUD) is critical, especially when these individuals transition out of correctional facilities and back into their communities. Unfortunately, few formerly incarcerated individuals use MOUD upon community reentry, often due to challenges with accessing treatment. As a result, this population remains at high risk of overdose and/or rearrest. In Wisconsin, community pharmacists are a promising resource for improving access and use of MOUD among formerly incarcerated individuals, specifically by administering injectable naltrexone. However, community pharmacists remain underutilized due to several barriers across the socioecological scale. Accordingly, this study used a participatory approach to explore strategies for addressing these barriers and connecting formerly incarcerated individuals to community pharmacist-administered injectable naltrexone.MethodsFive community pharmacists with experience administering injectable naltrexone and treating formerly incarcerated patients participated in three iterative semi-structured focus groups. The focus groups were conducted virtually, and Mural, an online collaborative whiteboard, was used to take notes on each focus group. Respectively, the goal of each focus group was to (1) discuss perceptions of existing barriers and prioritize barriers to be addressed based on perceived impact and feasibility, (2) identify and rank potential strategies for addressing the prioritized barriers based on perceived impact and feasibility, and (3) brainstorm strategy details/components and identify potential challenges related to the prioritized strategies. Focus groups were analyzed via deductive content analysis using a priori categories derived from the focus group goals.ResultsIn the first focus group, the participants prioritized two barriers to be addressed: lack of awareness of community pharmacist-administered injectable naltrexone services and lack of interagency collaboration among primary care clinics, community pharmacies, and correctional facilities. In the second focus group, the participants identified several strategies for addressing lack of awareness and/or lack of interagency collaboration, but prioritized pharmacist-led education targeted at correctional staff. Lastly, in the third focus group, the participants brainstormed several additional goals and topics for the educational strategy, including sharing existing resources, educating on required patient information, educating on providing patient information via prescriptions, establishing points of contact, emphasizing cost–benefits, and educating on the importance of insurance enrollment. Participants also identified potential challenges with the educational strategy, including inappropriate use of injectable naltrexone, time to implement educational sessions, and facilitating in-person meetings.DiscussionThe findings provide a first step toward better leveraging community pharmacist-administered injectable naltrexone for formerly incarcerated individuals.